2020
DOI: 10.3389/fnins.2020.00153
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Noise on the Behavioral and Neural Categorization of Speech

Abstract: We investigated whether the categorical perception (CP) of speech might also provide a mechanism that aids its perception in noise. We varied signal-to-noise ratio (SNR) [clear, 0 dB, −5 dB] while listeners classified an acoustic-phonetic continuum (/u/ to /a/). Noise-related changes in behavioral categorization were only observed at the lowest SNR. Event-related brain potentials (ERPs) differentiated category vs. category-ambiguous speech by the P2 wave (˜180-320 ms). Paralleling behavior, neural responses to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(51 citation statements)
references
References 105 publications
(206 reference statements)
9
40
0
Order By: Relevance
“…Adaptation studies-in which continuum sounds are presented repetitively and/or in serial order (Eimas and Corbit, 1973;Miller, 1975 causing a boundary shift in the direction toward the un-adapted detector at the polar end of the continuum (Rozsypal et al, 1985). As confirmed empirically, larger boundary shifts would be expected for less strongly categorized continua (Rozsypal et al, 1985), e.g., vowels vs. stop consonants (Altmann et al, 2014), acoustically degraded speech (Bidelman et al, 2020;, and for ambiguous speech tokens as shown here and previously (Ganong, 1980;Gow et al, 2008;Lam et al, 2017;Myers and Blumstein, 2008;Noe and Fischer-Baum, 2020).…”
Section: Discussionsupporting
confidence: 75%
“…Adaptation studies-in which continuum sounds are presented repetitively and/or in serial order (Eimas and Corbit, 1973;Miller, 1975 causing a boundary shift in the direction toward the un-adapted detector at the polar end of the continuum (Rozsypal et al, 1985). As confirmed empirically, larger boundary shifts would be expected for less strongly categorized continua (Rozsypal et al, 1985), e.g., vowels vs. stop consonants (Altmann et al, 2014), acoustically degraded speech (Bidelman et al, 2020;, and for ambiguous speech tokens as shown here and previously (Ganong, 1980;Gow et al, 2008;Lam et al, 2017;Myers and Blumstein, 2008;Noe and Fischer-Baum, 2020).…”
Section: Discussionsupporting
confidence: 75%
“…The introduction of acoustic degradation (i.e., noise) prolongs and weakens the ERPs, indicating predictable masking on speech processing (Bidelman and Howell, 2016;Bidelman et al, 2018;Billings et al, 2009). However, we have recently shown that speech categories-those carrying a strong phonetic identity-are more resilient to noise degradation than their phonetically ambiguous counterparts (Bidelman et al, 2020a). Categorization recruits a wide variety of frontal, temporal, and parietal brain regions (Al-Fahad et al, 2020;Chang et al, 2010;Myers et al, 2009).…”
Section: Introductionmentioning
confidence: 93%
“…Forty-nine young adults (male: 15, female: 34; aged 18 to 33 years) were recruited as participants from the University of Memphis student body to participate into our ongoing studies on the neural basis of speech perception and auditory categorization (Bidelman et al, 2020b;Bidelman & Walker, 2017b;Mankel et al, 2020). All participants had normal hearing sensitivity (i.e., <25 dB HL between 500-2000 Hz).…”
Section: Participantsmentioning
confidence: 99%
“…Since we were interested to decode prototypical (Tk1/5) from ambiguous speech (Tk3)a marker of categorical processing (Bidelman, 2015;Bidelman & Walker, 2019b;Liebenthal et 10 al., 2010b)-we merged Tk1 and Tk5 responses since they reflect prototypical vowel categories ("u" vs. "a'). In contrast, Tk3 reflects a bistable percept-an category-ambiguous sound listeners sometimes label as "u" or "a" (Bidelman et al, 2020a;Bidelman & Walker, 2017b;Mankel et al, 2020). To ensure an equal number of trials and signal to noise ratio (SNR) for prototypical and ambiguous stimuli, we considered only 50% of the data from the merged (Tk1/5) samples.…”
Section: Eeg Source Localizationmentioning
confidence: 99%
See 1 more Smart Citation